Industrial social work : an exploration and an assessment of the practice of social work in industry in South Africa - Rankin, Pedro (Rhodes University, Faculty of Humanities, Department of Social Work, 1992)
Industries in South Africa have been employing social workers in increasing numbers during the last decade, and in several of the bigger industries social work seem to have succeeded in establishing itself over the course of time. Certain forces seem to be operating in both industry and social work which could facilitate the introduction and development of industrial social work as a specialised field of practice in South Africa. Very significant variables in this regard are a rapidly changing labour force, and certain socio-political developments in South Africa, that took place especially during the last decade, and in particular during the past two years. A lack of knowledge about the practice of social work in industry exists in South Africa, mainly as a result of a general lack of empirical research into this field. The main purpose of this research project was to add to the knowledge about the nature of industrial social work practice in South Africa, and to contribute to an understanding of the forces influencing its development. In order to achieve this overall purpose, an extensive review of the existing literature was done with the aim of identifying and describing the present trends and issues in industrial social work thinking. This was combined with an empirical investigation into the practice of social workers presently employed in industry in South Africa. In addition to this, the attitude of industries not employing social workers was established with a view of determining factors influencing the further development of industrial social work. A third component of the empirical investigation consisted of a survey of the attitudes and knowledge of community welfare organisations regarding industrial social work practice. This was done in an effort to establish the amount of support for industrial social work from the rest of the profession. The findings of the empirical investigation indicated an emphasis on the individual employee as far as the practice of industrial social work is concerned - an EAP model thus. Industries not employing social workers still seem to need more education as far as the true nature of social work practice is concerned, and there seem to be a reserved acceptance of industrial social work practice amongst community welfare organisations, as well as a lack of knowledge. In conclusion it can be stated that the social work fraternity in South Africa should take more serious notice of occupational social work practice in South Africa in general, and of industrial social work practice in particular, mainly because of its importance to the worker.
Keywords: Uncatalogued